ANALISIS NILAI PENDIDIKAN SOSIAL YANG TERKANDUNG DRAMA LAKON SARIDIN ANDUM WARIS VERSI KETOPRAK WAHYU MANGGOLO - Aprilia, Sinta Dewi; Fajrie, Nur; Rondli, Wawan Shokib (Universitas Muria Kudus, 2025)
This study aims to analyze the value of social education in the drama of Saridin Andum Waris version of Ketoprak Wahyu Manggolo. This study is a qualitative study with a content analysis approach. This study focuses on the identification and understanding of social values conveyed through ketoprak performances. Data were collected through observation, documentation, and interviews with members of the ketoprak group. The data analysis technique used content analysis. The data validation using member check. The results of the study concluded that this drama contains important values such as responsibility, honesty, empathy, and cooperation. Through the unique and silly character of Saridin, the audience is taught about moral and ethical principles in a social context. Ketoprak Wahyu Manggolo, with its contemporary adaptation, still plays an important role in conveying social messages and preserving traditional culture. This study concludes that ketoprak as a medium for social education can strengthen the understanding of moral and cultural values in society.